PENDIDIKAN KARAKTER PADA ANAK USIA DINI DALAM PERSPEKTIF ISLAM - Kahar, M. Iksan (Pusat Studi Gender dan Anak, IAIN Palu, 2019)
The cultivation of character values ​​in children is absolutely necessary with the aim of developing the child's basic potential so that he grows into a person who is good-hearted, well-thought and well-behaved. In essence, early childhood have different characteristics when compared to adults, early childhood have a high enough curiosity, like to play, imitate and imagine. It is through these characteristics that will be used as a foothold in instilling character values ​​in these early childhood. Implementation of character education in schools in early childhood can be done through center-based learning that is beam centers, role playing centers, Qur'an centers, preparation centers and skills centers. The three centers are interrelated with one another which will make students have character in accordance with Islamic values.